2021
DOI: 10.1371/journal.pone.0251291
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of manual therapy for chronic obstructive pulmonary disease: A systematic review

Abstract: Background Manual therapy (MT) can be beneficial in the management of chronic obstructive pulmonary disease (COPD). However, evidence of the efficacy of MT for COPD is not clear. Therefore, we aimed to review the effects of MT, including Chuna, in people diagnosed with COPD. Methods MEDLINE via PubMed, EMBASE, The Cochrane Central Register of Controlled Trials (CENTRAL), China National Knowledge Database (CNKI), KoreaMed, Korean Medical Database (KMbase), and Oriental Medicine Advanced Searching Integrated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…MT plays a role in expanding the rib cage and reducing respiratory muscle shortening [30] . Studies have shown a major effect on the improvement of motor performance in patients with COPD [16] . The CMT used in this study is a technique involving 10 to 15 minutes of exercise conducted by a trained professional Korean medicine doctor, and as the patient can receive the therapy while lying on the bed, the technique is advantageous in that it can be performed regardless of the severity of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…MT plays a role in expanding the rib cage and reducing respiratory muscle shortening [30] . Studies have shown a major effect on the improvement of motor performance in patients with COPD [16] . The CMT used in this study is a technique involving 10 to 15 minutes of exercise conducted by a trained professional Korean medicine doctor, and as the patient can receive the therapy while lying on the bed, the technique is advantageous in that it can be performed regardless of the severity of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The osteopathic approach for patients with COPD, combined with rehabilitation and pharmacological treatments, could demonstrate a greater benefit for this clinical setting. In the literature, there is no univocity in stating that OMT is absolutely valid for respiratory patients [ 14 ]. The multiple explanations of the positive results obtained are always linked to structural factors, such as the improvement of the movement of the ribcage (joints and muscles) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there is no univocity in stating that OMT is absolutely valid for respiratory patients [ 14 ]. The multiple explanations of the positive results obtained are always linked to structural factors, such as the improvement of the movement of the ribcage (joints and muscles) [ 14 ]. Osteopathy in cardiac surgery patients, undergoing median sternotomy, has highlighted several benefits, including an increase in the pain threshold [ 1 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, manual therapy has been widely used as complementary alternative medicine to manage musculoskeletal pain [ 2 ]. Many studies have shown the efficacy of CMT [ 3 , 4 , 5 , 6 , 7 ]. Consequently, CMT was included in the coverage of the National Health Insurance of Korea in 2019.…”
Section: Introductionmentioning
confidence: 99%